Deep structure of the Antarctic plate's boundary zone along midocean ridges on the cross-sections and lateral slices - R. Kh. Greku; T. R. Greku (Ukrainian Antarctic Journal, 2009)
3D vertical structure of the Antarctic Plate's boundary along longitudinal cross-sections and lateral slices at different depths is displayed through a distribution of density anomalies using the harmonic coefficients of the EGM96 geoid model. Features of interaction between the Antarctic Plate and other plates are shown with our gravimetric tomography data over more than 40,000 km along the palte boundary. Two bodies (plumes) dominate in the mantle. Less dense masses ascend from depth of 2800 km and then split up at the depth of 200 km as three branches to the Australian-Antarctic Discordance (AAD), the Ross Sea and the Nazca plate. Dense masses descend from a surface as subducted slabs and collect at depths of 60 km and 280 km. It was discovered in the AAD area and the Nazca Ridge that thinning hot masses penetrate into the colder crust and lithosphere.